BREXIT REFERENDUM OF EUROPEAN UNION - Laode Muhamad Fathun (Universitas Jenderal Ahmad Yani, 2020)
This paper describes the phenomenon Brexit or Britain Exit on the future of EU regionalism and its impact on Indonesia. This paper will explain in detail the reason for the emergence of a number of policies Brexit. Brexit event caused much speculation related to Brexit in the European Union. The policy is considered full controversial, some experts say that Brexit in the European Union (EU) showed the independence of Britain as an independent state. Other hand, that Britain is the